ASSESSMENT OF IMPLEMENTATION OF THE PHILIPPINES’ EXPANDED BREASTFEEDING PROMOTION ACT OF 2009 (REPUBLIC ACT NO. (Proceedings of the International Conference on Public Health, 2017)
Malnutrition among 0 to 5 year old Filipino children is persisting. Translation of Republic Act No. 10028 or the Philippines’ Expanded Breastfeeding Promotion Act of 2009 is vital towards enhancing efforts in addressing the first 1,000 days critical period in infancy and early childhood. The study reviewed and analyzed the status of the law in terms of its implementation, determined enhancing and hindering factors for its implementation using focus group discussions and key informant interviews among various entities known to play a key role in the implementation of R.A. No. 10028 based on the implementing rules and regulation (IRR).  Based on the evaluation criteria developed, there were aspects in the IRR that remain “unclear” or were “present, but with questions”. Knowledge and understanding of the law among program implementers varied.  Awareness, information dissemination, advocacy and promotion as well as partnerships and commitments facilitate implementation of the law. On the other hand, the absence of a monitoring and evaluation system, unavailability of resources in the form of financial, materials, manpower, carrying capacity of focal persons and agencies and commitments of local government units hinder its implementation. A Joint Memorandum Circular enjoining partner-implementers to their full participation according to identified roles and tasks in the IRR are keys to the law’s operationalization. Research participants voiced the need for the review of the policy, a “re-assembly” of the national working group on infant and young child feeding (IYCF) program and the creation of an oversight committee on the implementation of the law.
Keywords: Filipino children, breastfeeding promotion, Philippines